PELAKSANAAN PEMBANGUNAN INFRASTRUKTUR JALAN DESA DUSUN TUA PELANG KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU TAHUN 2020-2022 - Exposto, Indy Maya; Marta, Auradian (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The background to the problem in this research is the implementation of road infrastructure development in Dusun Tua Pelang Village, Kelayang District, Indragiri Hulu Regency in 2020,2021,2022. Construction of road infrastructure in Dusun Tua Pelang Village began in 2020, but until 2022 it had not been completed. This raises the question of factors influencing this development. The aim of this research is to describe the implementation of road infrastructure development in Dusun Tua Pelang Village. This research method uses a qualitative approach with a descriptive research type. The location of this research is in Dusun Tua Pelang Village, Kelayang District, Indragiri Hulu Regency. This research uses data such as village development planning, village budget data for development, and data on damaged roads. The data collection technique is by conducting interviews and collecting documentation. The results and conclusions of this research are factors that influence the implementation of development, namely, firstly, human resources are village government officials who lack supervision over the implementation of development so that it is less than optimal. The village government is also less precise in allocating the budget. Second, financial resources, namely the budget owned by Dusun Tua Pelang, are still lacking so that the implementation of development is not optimal. Third, technical problems occur because they are hampered by inappropriate planning and workers are slow in carrying out development. Governance of Dusun Tua Pelang village government does not carry out planning well and there is a lack of community participation. So, the most influencing factors in this research are human resources. Keyword : implementation, development, infrastructure